Validation of prostate‐specific antigen laboratory values recorded in Surveillance, Epidemiology, and End Results registries. Issue 4 (26th October 2016) - ; Adamo, Margaret (Peggy); Boten, Jessica A.; Coyle, Linda M.; Cronin, Kathleen A.; Lam, Clara J. K.; Negoita, Serban; Penberthy, Lynne; Stevens, Jennifer L.; Ward, Kevin C.
Abstract : BACKGROUND: Researchers have used prostate‐specific antigen (PSA) values collected by central cancer registries to evaluate tumors for potential aggressive clinical disease. An independent study collecting PSA values suggested a high error rate (18%) related to implied decimal points. To evaluate the error rate in the Surveillance, Epidemiology, and End Results (SEER) program, a comprehensive review of PSA values recorded across all SEER registries was performed. METHODS: Consolidated PSA values for eligible prostate cancer cases in SEER registries were reviewed and compared with text documentation from abstracted records. Four types of classification errors were identified: implied decimal point errors, abstraction or coding implementation errors, nonsignificant errors, and changes related to "unknown" values. RESULTS: A total of 50, 277 prostate cancer cases diagnosed in 2012 were reviewed. Approximately 94.15% of cases did not have meaningful changes (85.85% correct, 5.58% with a nonsignificant change of <1 ng/mL, and 2.80% with no clinical change). Approximately 5.70% of cases had meaningful changes (1.93% due to implied decimal point errors, 1.54% due to abstract or coding errors, and 2.23% due to errors related to unknown categories). Only 419 of the original 50, 277 cases (0.83%) resulted in a change in disease stage due to a corrected PSA value. CONCLUSIONS: The implied decimal error rate was only 1.93% of all cases in the current validation study, with a meaningful error rate of 5.81%. The reasons for the lower error rate in SEER are likely due to ongoing and rigorous quality control and visual editing processes by the central registries. The SEER program currently is reviewing and correcting PSA values back to 2004 and will re‐release these data in the public use research file. Cancer 2017;123:697–703. © 2016 American Cancer Society . Abstract : Researchers have used prostate‐specific antigen (PSA) values collected by central cancer registries to evaluate tumors for potential aggressive clinical disease. The current study describes the comprehensive review of PSA laboratory values recorded across all Surveillance, Epidemiology, and End Results registries for 2012 prostate cancer cases and the proposed mechanism for reviewing and correcting PSA laboratory values.